Factors Influencing Complaints Of Musculoskeletal Disorders (MSDS) On Female Transport Workers “Tukang Suun” At Badung-Kumbasari Market - Wira Natanagara, I Gede Catur; Indonesiani, Suyasning Hastiko (Devotion : Journal of Research and Community Service, 2022)
Work as a transport worker or "manufacturer" is one of the jobs at risk of musculoskeletal disorders (MSDs). Complaints are caused by various factors such as age, years of service, workload, and hauling distance. This study aims to determine the effect of age, years of service, weight of load, and distance of transport with musculoskeletal complaints. The research location was carried out in Badung-Kumbasari Market, Denpasar City with a cross sectional method.  The design used in this study is a cross sectional study. Data collection was carried out from September-December 2016The sample of this study was taken consecutively with 32 women as respondents. Musculoskeletal complaints were measured using a Nordic Body Maps questionnaire with a Likert scale and the factors to be studied were using questionnaires and tools that had been prepared. Data analysis used the Pearson correlation test. From the results of the study, it was found that there was a relationship between age and musculoskeletal complaints (r*=0.625; p<0.001), the relationship between years of service and musculoskeletal complaints (r*=0.683; p<0.001), the relationship between the weight of the load and musculoskeletal complaints (r*= 0.731; p<0.001) and the relationship between haulage distance and musculoskeletal complaints (r*=-0.528; p<0.001). It can be concluded that age, working period, weight of load and hauling distance affect MSDs in haulage workers and weight of load is the dominant factor. It is hoped that ergonomic weight control can reduce musculoskeletal complaints in female transport workers.